On the role of the single currency ECU - Sinimaaria Ranki (Bank of Finland, 1995)
International money is used as a medium of exchange, as a unit of account, and as a store of value.These roles can be performed either in the private or in the public sector of the economy.In order to be considered in the decision making of international agents, the currency must fulfil some preconditions.These are the stability property of the currency, the financial market structure in the issuing country, and the transaction domain of the currency. Once the currency has become internationally used, some benefits and costs accrue to the issuing country.The extent of the benefits and costs depends on the symmetry of the international monetary system, on the prevailing exchange rate regime, and on the provision of international liquidity.In a world with floating exchange rates, the most remarkable benefit stems from the ability of domestic traders to pass the exchange rate risk for foreigners.Also lower transaction costs due to larger trading volumes will benefit domestic agents.The main cost, on the other hand, stems from the difficulty to control the exchange rate.The price of a major international currency is determined by supply and demand, that do not always reflect the macroeconomic stance in the issuer country. Previous experiences with internationally used currencies have shown that several developments can be identified that together imply a growing role for an international currency.Firstly, the importance of a currency has increased as a result of a stable inflation performance and a credible monetary policy. Although the objective of price stability is the explicit target of the monetary policy conducted by the ECB, it will take some time for the ECB to establish the credibility in implementing policy commitments.Secondly, a wide menu of financial instruments and lifting of capital controls has increased the popularity of the currency.The financial market in EMU will evidently be thicker than the market for any of the current EU currencies.Finally, a growing share in world trade has resulted in an increased use of the currency.The transaction domain of the single currency ECU is inherited from the current national currencies.Because of the remarkable size of EMU in world trade, the ECU could also be expected to rapidly become an important invoicing currency, which also strengthens the efficient working of the financial market.But even if the potential of the ECU to become the major international currency would be beneficial for such an evolution, the position of the USD in the international monetary system will be determining.As long as international investors see no reason to give up the use of the USD, it is extremely hard for the ECU to challenge the role of the USD as the key currency.
URN:NBN:fi:bof-20140807502
Keywords: 330